2020
DOI: 10.1088/1748-9326/abafd5
|View full text |Cite
|
Sign up to set email alerts
|

High potential for loss of permafrost landforms in a changing climate

Abstract: The presence of ground ice in Arctic soils exerts a major effect on permafrost hydrology and ecology, and factors prominently into geomorphic landform development. As most ground ice has accumulated in near-surface permafrost, it is sensitive to variations in atmospheric conditions. Typical and regionally widespread permafrost landforms such as pingos, ice-wedge polygons, and rock glaciers are closely tied to ground ice. However, under ongoing climate change, suitable environmental spaces for preserving landfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 76 publications
1
29
0
Order By: Relevance
“…Today, we see continuing evidence of this pattern with elevationally or latitudinally disjunct populations of some species in CRL-linked habitats (Fickert et al, 2007;Růžička & Zacharda, 1994). Thus, evidence from both the past and present strengthens the prediction that CRLs will sustain long-lasting cold refugia under contemporary climate change (Caccianiga et al, 2011;Gobbi et al, 2014;Millar et al, 2015;; but see Karjalainen et al, 2020).…”
Section: Lessons From the Pastmentioning
confidence: 62%
“…Today, we see continuing evidence of this pattern with elevationally or latitudinally disjunct populations of some species in CRL-linked habitats (Fickert et al, 2007;Růžička & Zacharda, 1994). Thus, evidence from both the past and present strengthens the prediction that CRLs will sustain long-lasting cold refugia under contemporary climate change (Caccianiga et al, 2011;Gobbi et al, 2014;Millar et al, 2015;; but see Karjalainen et al, 2020).…”
Section: Lessons From the Pastmentioning
confidence: 62%
“…Several studies have shown the potential of statistical modeling to estimate permafrost distribution (Aalto, Karjalainen, et al., 2018; Boeckli et al., 2012; Etzelmüller et al., 2001; Gruber & Hoelzle, 2001) and to capture the multivariate nature of periglacial processes at landscape‐scale by documenting how their distribution and dynamics are influenced by environmental factors (Hjort & Luoto, 2011, 2013; Hjort et al., 2014; Karjalainen et al., 2019; Rudy et al., 2017). By statistically identifying the variables influencing the ground thermal regime and periglacial processes, it becomes possible to better explain their current distribution and predict their future evolution based on climate change scenarios (Aalto et al., 2017; Blois et al., 2013; Hjort et al., 2018; Karjalainen et al., 2020). However, previous research has been primarily based on in‐situ measurements (e.g., ground temperature from boreholes) or mapped landforms (e.g., inventory of solifluction lobes and palsas) and few studies have integrated advanced remote sensing data documenting periglacial activity, such as InSAR‐based ground velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Rock glaciers, defined here as creeping permafrost landforms consisting of an ice/rock mixture (Berthling, 2011), are often used as a proxy for permafrost occurrence or paleo-permafrost extent (Lilleøren and Etzelmüller, 2011;Scotti et al, 2013;Etzelmüller et al, 2020;Karjalainen et al, 2020). In mountainous areas where large topographic variability and site-specific conditions determine the local occurrence of permafrost, rock glacier inventories are valuable to complement global kilometric-resolution permafrost products (Obu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%